FOODLIT-tool: Development and validation of the adaptable food literacy tool towards global sustainability within food systems - Rosas, Raquel (2022)
Facing multiple anthropogenic challenges and considering the current global pandemic, food sustainability is stated as threatened by major intergovernmental agencies. Given the heterogeneity of food systems, the need to enhance food-related behaviours by promoting the acquisition of knowledge and competencies, and the demand to involve stakeholder's diversity, this study aims to develop and validate an instrument that measures food literacy (FL), its determinants and its influential factors in an adult sample. Based on the Food Literacy Wheel (FLW) framework and integrated within the FOODLIT-PRO - Food Literacy Project, this study has three phases and a total of 2406 participants: (1) item development and content validity, (2) instrument development entailing item reduction strategies, factor extraction methodologies (exploratory and confirmatory analyses) and sensitivity testing, with two samples of a total of 1447 adults, and (3) instrument validation encompassing tests of dimensionality (confirmatory factor analysis), reliability (composite reliability) and validity (convergent and discriminant validity), and measure invariance testing, with 959 adults. Concerning statistical and psychometric properties, (1) a pool of 40 items (26 for FL; single items: five for determinants and nine for influential factors) was developed with inductive and deductive methodologies and reflected the FLW, (2) a 5-factor structure was explored, demonstrated acceptable model fit, and good sensitivity indices, and (3) a 5-dimensional reliable structure with 24 items was validated, configural invariance was achieved, and convergent and discriminant validity were significant in most dimensions. The FOODLIT-Tool contributes with an innovative measure of FL in adults that allows for a tailored assessment when approaching food-related issues within global food systems, providing a multidisciplinary tool that can be cross-widely applied to promote food-related behaviour change.